CNTNAP1 Mutations and Their Clinical Presentations: New Case Report and Systematic Review. (13th April 2020) - Sabbagh, Sandra; Antoun, Stephanie; Mégarbané, André
Abstract : Lethal congenital contracture syndrome type 7 (LCCS7) and congenital hypomyelinating neuropathy type 3 (CHN3) are rare autosomal recessive diseases, characterized by severe neonatal hypotonia, polyhydramnios, arthrogryposis, facial diplegia, and severe motor paralysis, leading to death in early infancy. They are related to mutations in the CNTNAP1 (contactin associated protein 1) gene, playing an important role in myelination. Recent studies have shown that both diseases could present with a wide phenotypic spectrum, with promising survival up to early childhood. We report on a 7-year-old boy from a nonconsanguineous Lebanese family presenting with neonatal hypotonia, respiratory distress, and arthrogryposis. Molecular analysis revealed the presence of a pathogenic variant in the CNTNAP1 gene leading to a premature stop codon: NM_003632.2:c.3361C>T p.(Arg1121 ∗ ). A review of the literature is discussed.